FLORAL AND REPRODUCTIVE PHENOLOGY OF ALOE VERA - A. H. RATHOD; S. K. PARMAR; P. O. VAGHELA; W. A. SHEIKH (The Bioscan, 2014)
The studies on floral and reproductive phenology in Aloe vera revealed that peak flowering period was ranged from last week of November to second week of December. Brightly colored tubular flowers developed on cylindrical raceme. The flowers are bisexual, containing both female and male parts. The perianth is of 6 lobes, in which sepals and petals are considered together. The flower comprises of 6 stamens and the ovary is superior, where the sepals, petals and stamens are inserted beneath the ovary. Anthesis period is of 5 to 10 days within raceme, start from 7.00 am and continued up to 3.00 pm. The receptivity of stigma was observed high at anthesis. The peak period of dehiscence observed from 10.00 to 12.00. The fruits Aloe vera matures within 60 to 67 days.